Controlling the Cassie-to-Wenzel Transition: an Easy Route towards the Realization of Tridimensional Arrays of Biological Objects - Ciasca, G.; Papi, M.; Chiarpotto, M.; Ninno, A. De; Giovine, E.; Campi, G.; Gerardino, A.; Spirito, M.De; Businaro, L. (Nano-Micro Letters, 2014)
In this paper we provide evidence that the Cassie-to-Wenzel transition, despite its detrimental effects on the wetting properties of superhydrophobic surfaces, can be exploited as an effective micro-fabrication strategy to obtain highly ordered arrays of biological objects. To this purpose we fabricated a patterned surface wetted in the Cassie state, where we deposited a droplet containing genomic DNA. We observed that, when the droplet wets the surface in the Cassie state, an array of DNA filaments pinned on the top edges between pillars is formed. Conversely, when the Cassie-to-Wenzel transition occurs, DNA can be pinned at different height between pillars. These results open the way to the realization of tridimensional arrays of biological objects.